2020
DOI: 10.3390/d12030108
|View full text |Cite
|
Sign up to set email alerts
|

New Records of Antarctic Tardigrada with Comments on Interpopulation Variability of the Paramacrobiotus fairbanksi Schill, Förster, Dandekar and Wolf, 2010

Abstract: Studies on Antarctic tardigrades started at the beginning of the twentieth century and have progressed very slowly and ca. 75 tardigrade species are known from this region. Paramacrobiotus fairbanksi was described from USA based on genetic markers and later reported from Italy, Poland, and Spain. The “everything is everywhere” hypothesis suggests that microscopic organisms have specific features which help them to inhabit most of environments and due to this they can be considered cosmopolitan. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…In contrast to many widespread Milnesium species, wide ranges of rotifer species are not hypothesised to be human mediated (Fontaneto et al, 2008 ). Moreover, whereas widespread tardigrade species are more often found to have pantropical distributions (Gąsiorek, Jackson, et al, 2019 ; Gąsiorek et al, in review) rather than disjunct temperate ranges in the northern and southern hemisphere (Gąsiorek, Vončina, et al, 2019 ; Kaczmarek et al, 2020 ), the precedence of pantropical distributions has not been found in rotifers (see Fontaneto et al, 2008 ; Jaturapruek et al, 2018 ), as some temperate widespread species were found, e.g., in Europe, Africa and New Zealand. Importantly, we have not identified such disjunct temperate distributions in Milnesium that are likely to be natural (see subsection 4.1.1 above).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to many widespread Milnesium species, wide ranges of rotifer species are not hypothesised to be human mediated (Fontaneto et al, 2008 ). Moreover, whereas widespread tardigrade species are more often found to have pantropical distributions (Gąsiorek, Jackson, et al, 2019 ; Gąsiorek et al, in review) rather than disjunct temperate ranges in the northern and southern hemisphere (Gąsiorek, Vončina, et al, 2019 ; Kaczmarek et al, 2020 ), the precedence of pantropical distributions has not been found in rotifers (see Fontaneto et al, 2008 ; Jaturapruek et al, 2018 ), as some temperate widespread species were found, e.g., in Europe, Africa and New Zealand. Importantly, we have not identified such disjunct temperate distributions in Milnesium that are likely to be natural (see subsection 4.1.1 above).…”
Section: Discussionmentioning
confidence: 99%
“…Guil, 2011; Pilato & Binda, 2001), but only a limited number of geographically and/or taxonomically restricted studies on this subject have so far been conducted (e.g. Cesari et al, 2016; Gąsiorek, Jackson, et al, 2019; Gąsiorek et al, 2020; Guil et al, 2009; Jørgensen et al, 2007; Kaczmarek et al, 2020; Morek & Michalczyk, 2020; Morek et al, 2019). Nevertheless, these initial studies already indicate that many species may not be as widely distributed as previously assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Antarctic tardigrades started at the beginning of the twentieth century and have progressed slowly up to the present. Currently, 71 tardigrades have been reported from the continental Antarctic and the Antarctic Peninsula, and a few from other regions (for review, see Convey & McInnes 2005;and later publications:;Binda et al 2005;McInnes 2010;Pilato et al 2012;Guidetti et al 2014;Kaczmarek et al 2014;Tsujimoto et al 2014;Velasco-Castrillón et al 2014;Vecchi et al 2016;Guidetti et al 2017;Pilato et al 2017;Dastych 2018;Kaczmarek et al 2018Kaczmarek et al , 2020aKihm et al 2020;Tsujimoto et al 2020).…”
Section: Redescription Of Antarctic Eutardigrade Dastychius Improvisusmentioning
confidence: 99%
“…Still little is known on the genetic diversity of tardigrade species with confirmed wide distribution (Jørgensen, Mobjerg and Kristensen, 2007;Jørgensen et al, 2013;Cesari, Bertolani, Rebecchi and Guidetti, 2009;Cesari et al, 2016;Gąsiorek et al, 2016, Gąsiorek, Blagden andZawierucha et al, 2018;Jackson and Meyer, 2019;Kaczmarek et al, 2020;Pogwizd and Stec, 2020;Sugiura, Arakawa and Matsumoto, 2020;Sugiura, Minato, Matsumoto and Suzuki, 2020).…”
Section: Zoologymentioning
confidence: 99%